LAYANAN CHATBOT PADA BAKTI KOMINFO WILAYAH KERJA IV SURABAYA - Choireza Rizaldi; Dwi Cahyono (PT. Jurnal Center Indonesia Publisher, 2024)
System chatbot at the Kominfo service agency that will help process sentences based on keywords or phrases to get the desired information to facilitate service. The customer service agent system is divided into 3 parts, namely responder, classifier, and graphmaster. Responder is the part that connects the bot with the user. The task of the responder is to transfer data from the user to the classifier and control the input and output. The classifier is the part that filters and normalizes the input and performs segmentation of the sentences that have been inputted. Graphmaster is the part that matches the input pattern to the facts that have been created.